Narcissus Plants: A Melting Pot of Potyviruses - Wiwit Probowati; Shusuke Kawakubo; Kazusato Ohshima (Viruses, 2022)
Our paper presents detailed evolutionary analyses of narcissus viruses from wild and domesticated Narcissus plants in Japan. Narcissus late season yellows virus (NLSYV) and narcissus degeneration virus (NDV) are major viruses of Narcissus plants, causing serious disease outbreaks in Japan. In this study, we collected Narcissus plants showing mosaic or striped leaves along with asymptomatic plants in Japan for evolutionary analyses. Our findings show that (1) NLSYV is widely distributed, whereas the distribution of NDV is limited to the southwest parts of Japan; (2) the genomes of NLSYV isolates share nucleotide identities of around 82%, whereas those of NDV isolates are around 94%; (3) three novel recombination type patterns were found in NLSYV; (4) NLSYV comprises at least five distinct phylogenetic groups whereas NDV has two; and (5) infection with narcissus viruses often occur as co-infection with different viruses, different isolates of the same virus, and in the presence of quasispecies (mutant clouds) of the same virus in nature. Therefore, the wild and domesticated Narcissus plants in Japan are somewhat like a melting pot of potyviruses and other viruses.